Software Proteus y su incidencia en el aprendizaje de Circuitos Eléctricos en los estudiantes de segundo de Bachillerato General Unificado - Guallán Sárate, María Fernanda (2022)
The use of information and communication technologies (ICT) today is essential to address content related to the subject of Physics, giving rise to this research work that aimed to determine the impact of the use of Proteus software in the learning of Parallel Electrical Circuits in the second year of General Unified High School students in the Fernando Daquilema Educational Unit in the academic period 2021-2022. This is a quasi-experimental design study in which two groups were used for the study, it had a quantitative approach since it will be based on statistics, and the research level was explanatory. The population was constituted by students of the second year of unified general high school, taking from there a non-probabilistic sample of intentional type of fifty-eight students, half of them being the quasi-experimental group and the other half the control group. The instrument used for data collection was the objective test, information was collected before and after the application of the software and the traditional class, which consisted of ten questions. Once the Proteus software was used and the traditional class was dictated in the respective groups, the comparison of means was made and it was obtained that the means are different with 8.02 in the quasi-experimental group where the students reach the required learning, on the contrary with 5.85 in the control group where the teachers are close to reach the required learning, concluding that the use of the Proteus software affects the learning of Parallel Electrical Circuits in the students of the second year of General Unified High School. Finally, it is recommended to teachers to use simulators in the subject of Physics starting from the explanation of the elements of the software, thus generating motivation and interest in the students and improving their learning.